Answer :

Answer:

0

Step-by-step explanation:

We have the fraction [tex]\frac{2m}{2m+3} -\frac{2m}{2m-3}[/tex]

Step 1. Use LCM of the fraction, (2m+3)(2m-3), to simplify the fraction:

[tex]\frac{(2m-3)(2m)-(2m+3)(2m)}{(2m+3)(2m-3)} =\frac{2m^2-6m-[2m^2+6m]}{(2m+3)(2m-3)} =\frac{2m^2-6m-2m^2-6m}{(2m+3)(2m-3)} =\frac{-12m}{(2m+3)(2m-3)}[/tex]

Step 2. Equate the resulting fraction to zero and solve for [tex]m[/tex]:

[tex]\frac{-12m}{(2m+3)(2m-3)} =0[/tex]

[tex]-12m=0[(2m+3)(2m-3)][/tex]

[tex]-12m=0[/tex]

[tex]m=\frac{0}{-12}[/tex]

[tex]m=0[/tex]

Step 3. Replace the value in the original equation and check if it holds:

[tex]\frac{-12m}{(2m+3)(2m-3)} =0[/tex]

[tex]-12m=0[/tex]

Since [tex]m=0[/tex],

[tex]-12(0)=0[/tex]

[tex]0=0[/tex]

Since the only solution of the equation holds, the equation bellow doesn't have any extraneous solution

adioabiola

The number of extraneous solution the equation has is 1

Given:

StartFraction 2 m Over 2 m + 3 EndFraction minus StartFraction 2 m Over 2 m minus 3 EndFraction

[tex] = \frac{2m}{2m + 3} - \frac{2m}{2m - 3} [/tex]

solve by finding the lcm first

[tex] = \frac{2m(2m - 3) - 2m(2m + 3)}{(2m + 3) (2m - 3)} [/tex]

= 4m² - 6m - 4m² - 6m / 4m² - 6m + 6m - 9

= - 12m / 4m² - 9

  • equate to 0

0 = 12m / (4m² - 9)

  • cross product

0 × (4m² - 9) = 12m

0 = 12m

m = 0/12

m = 0

Therefore, the number of extraneous solution the equation has is 1

Learn more about extraneous solution:

https://brainly.com/question/2959656

Other Questions